Digital Transformation and Resilient Business Models: Unlocking Competitive Advantage in Post-Pandemic SMEs - Kusuma, Sitta (SAFE-Network, 2025)
This study explores the role of digital transformation in enhancing the resilience and competitive advantage of Small and Medium Enterprises (SMEs) in the post-pandemic era. Through both qualitative and quantitative analyses, the study examines how SMEs have adopted digital technologies, such as e-commerce, cloud computing, and customer relationship management (CRM), to overcome challenges posed by the pandemic and build sustainable advantages. The findings reveal that digital transformation has a significant positive impact on business resilience, operational efficiency, and customer satisfaction. However, challenges such as limited skilled human resources and high initial investment costs remain barriers to full adoption. The study offers practical implications for SME owners and policymakers, emphasizing the need for strategic investments in digital skills and technology, as well as supportive policies to reduce barriers to digital transformation. Despite some limitations, the study contributes to the literature on resilient business models and the role of digital transformation in SMEs.